Bone metabolism, bone mineral content, and density in elite late teen female sprinters - Tsukahara, Y.; Torii, S.; Yamasawa, F.; Iwamoto, J.; Otsuka, T.; Goto, H.; Kusakabe, T.; Matsumoto, H.; Akama, T. (International Journal of Sports Medicine, 2021)
With intensive training, bone injuries are a major concern for athletes. To assess bone condition, we often measure bone turnover markers, bone mineral content and density; however, in junior athletes, it is not easy to distinguish changes caused by bone injuries from those caused by growth, because the metabolism is increased in both cases. Moreover, although some studies have examined female endurance athletes, knowledge regarding changes in static and dynamic bone conditions in late teen athletes is limited. In this study, we measured the bone mineral content and density, as well as bone turnover markers, in 40 elite female sprinters in their late teens. Whole body mode dual-energy X-ray absorptiometry was performed to measure bone mineral content and density. Blood samples were collected to determine bone resorption and formation markers at the end of track season in 2016 and during the same period of the following year. Body weight and bone mineral content significantly increased, and tartrate-resistant acid phosphatase type 5b, bone-type alkaline phosphatase, and osteocalcin significantly decreased after a year. Furthermore, the rate of change in bone mineral content was higher in younger athletes, indicating that bone growth approaches completion in the late teen years and that bone metabolism accordingly decreases.